Pengaruh Profitabilitas, Likuiditas, dan Aktivitas Terhadap Return Saham Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Ulisiyawati, Nur; Zulkifli, Makhmud (Management Department of Economics and Business Of Trunojoyo Madura University, 2024)
This research is a quantitative action research with a sample of 12 textile and garment companies. This research uses panel data regression because this research is a combination of cross section and time series data. So after doing the Chow and Hausman tests, it is known that the model used is the fixed effect. Panel data regression analysis was carried out to determine the direction and how much influence the independent variables have on the dependent variable. The results showed that a sample of 12 companies from 2017-2021 with 4 independent variables (company growth, company size, liquidity, profitability had an effect on variable Y (debt policy) simultaneously both had a simultaneous effect on debt policy. However, if seen from the effect partially, Firm Size (X2) has an effect on debt policy (Y) while other variables have no effect on debt policy.